2006
DOI: 10.1073/pnas.0602365103
|View full text |Cite
|
Sign up to set email alerts
|

Na + /monocarboxylate transport (SMCT) protein expression correlates with survival in colon cancer: Molecular characterization of SMCT

Abstract: We report an extensive characterization of the Na ؉ ͞monocarboxy-late transporter (SMCT), a plasma membrane protein that mediates active transport of monocarboxylates such as propionate and nicotinate, and we show that SMCT may play a role in colorectal cancer diagnosis. SMCT, the product of the SLC5A8 gene, is 70% similar to the Na ؉ ͞I ؊ symporter, the protein that mediates active I ؊ uptake in the basolateral surface of thyrocytes and other cells. SMCT was reported in the apical surface of thyrocytes and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
95
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 34 publications
6
95
1
Order By: Relevance
“…The other is SLC5A8 (human apical iodide transporter, hAIT), which was suggested to charge the release of iodide into the colloid across the apical membrane as an iodide channel [29,30]. However, this gene was found to serve as a sodium monocarboxylate transporter and does not mediate iodide uptake or efflux [31]. The actual actions of the PDS gene remain to be clearly demonstrated; however, PDS is primarily thought to mediate iodide efflux from cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…The other is SLC5A8 (human apical iodide transporter, hAIT), which was suggested to charge the release of iodide into the colloid across the apical membrane as an iodide channel [29,30]. However, this gene was found to serve as a sodium monocarboxylate transporter and does not mediate iodide uptake or efflux [31]. The actual actions of the PDS gene remain to be clearly demonstrated; however, PDS is primarily thought to mediate iodide efflux from cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SLC5A8 was designated human Apical Iodide Transporter (hAIT). Later it was shown that SLC5A8 overexpressed in Xenopus laevis oocytes mediates the sodium-coupled transport of monocarboxylates like L-lactate, propionate, butyrate, or nicotinate, whereas exposure to iodide or bromate did not lead to currents (7)(8)(9). The sodium-dependent transport of monocarboxylates by SLC5A8 was also corroborated in a mammalian expression system (10) leading to renaming of the molecule as Sodium Monocarboxylate Transporter 1 (SMCT 1).…”
mentioning
confidence: 87%
“…SLC5A8 methylation and transcriptional down-regulation has been linked to colon cancer susceptibility or to survival rates of colon cancer patients (9,15), and possible mechanisms for the tumor suppressive function have been suggested (32). Furthermore, there are reports on aberrant methylation of SLC5A8 in gastric cancer and on SLC5A8 silencing in papillary thyroid carcinomas (17) or glioma formation (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on transmembrane proteins and successfully identified NaGLT1, which mediates the tubular reabsorption of glucose and fructose (11,13). In addition, this database includes a Slc5a8, which was characterized as a monocarboxylate transporter, and is thought to be a tumor suppressor (27,31). Moreover, mouse Oatp5 was also identified (3).…”
Section: Discussionmentioning
confidence: 99%